AB0034 Activated neutrophils are able to efficiently produce interferon-alpha and retain this capability in systemic lupus erythematosus and rheumatoid arthritis patients. (23rd January 2014) - Lindau, D.; Rabsteyn, A.; Mussard, J.; Ribon, M.; Kötter, I.; Adema, G.; Boissier, M.-C.; Decker, P.
Abstract : Background: Neutrophils play a pivotal role in inflammation and contribute to systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) pathogenesis. Interferon (IFN)-α is involved in lupus development and might contribute locally to RA development. Activated plasmacytoid dendritic cells (pDC) are important producers of IFN-α but represent a minor cell population. On the other hand, neutrophils represent 50 % of total blood leukocytes. Objectives: Although neutrophils are not considered as IFN-α-producing cells, we have investigated whether they may produce this cytokine and the stimuli involved. Methods: PBMC and neutrophils were isolated from healthy individuals, SLE and RA patients. Mouse neutrophils were purified from the bone marrow. Cells were activated with different stimuli and IFN-α production/secretion was estimated by flow cytometry, ELISA and a bioassay. Neutrophil activation was verified by flow cytometry and ELISA. Gene expression was analyzed by qRT-PCR. Neutrophil extracellular trap (NET) induction was estimated by confocal microscopy. Chromatin, a major autoantigen in SLE also present in the synovial fluid of RA patients, was purified from calf thymus. We have actually previously shown that extracellular chromatin is pro-inflammatory. Results: Isolated neutrophils produce IFN-α upon stimulation with Toll-like receptor (TLR) 9 and TLR7/8 agonists. IFN-α secretion by neutrophils was observed with neutrophils from both healthy donors and SLE and RA patients. Similar results were obtained with mouse neutrophils. IFN-α production by neutrophils was associated with IL-8, IL-6 and TNF-α secretion, CD66b up-regulation, ROS production and increased gene expression levels of IFN-α, IFN-β and IL-6. In low responders, PBMC sustain IFN-α secretion by neutrophils in co-cultures. Neutrophil priming is not required but GM-CSF acts synergistically with TLR9 agonists. Particularly, neutrophils respond to all types (A, B and C) of CpG-oligonucleotides. pDC are more efficient than neutrophils in producing IFN-α at the single cell level but this was largely compensated by the 200-fold excess of neutrophils in whole blood. Importantly, neutrophil-derived IFN-α was detected in response to free extracellular chromatin and was associated with NET formation (NETosis). Conclusions: Neutrophils represent an important source of IFN-α. IFN-α was detected at the mRNA and protein levels and in an active and secreted form. Both normal as well as SLE and RA neutrophils produce IFN-α in response to specific stimuli. Therefore, neutrophils represent also important targets for future therapies aiming at influencing IFN-α levels. Disclosure of Interest: None Declared